2019
DOI: 10.1101/715292
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hippocampal Subfield Volumes in Abstinent Men and Women with a History of Alcohol Use Disorder

Abstract: Alcohol use disorder (AUD) has been associated with abnormalities in hippocampal volumes, but these relationships have not been fully explored with respect to sub-regional volumes, nor in association with individual characteristics such as gender differences, age, and memory. The present study examined the impact of those variables in relation to hippocampal subfield volumes in abstinent men and women with a history of AUD. Using Magnetic Resonance Imaging at 3 Tesla, we obtained brain images from 67 participa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…In a study of the sex effects of alcoholism on white matter microstructure, alcoholic males exhibited lower FA in the corpus callosum, SLF, arcuate fasciculus and external capsule compared to healthy controls, whereas alcoholic females exhibited higher FA in these regions compared to their control counterparts [Sawyer et al, 2018]. A recent substructural analysis from the same group showed that a longer duration of alcohol sobriety predicted larger volumes in the hippocampal CA1 for males, but smaller volumes in this region for females [Sawyer et al, 2019].…”
Section: Substance Use Disordersmentioning
confidence: 98%
“…In a study of the sex effects of alcoholism on white matter microstructure, alcoholic males exhibited lower FA in the corpus callosum, SLF, arcuate fasciculus and external capsule compared to healthy controls, whereas alcoholic females exhibited higher FA in these regions compared to their control counterparts [Sawyer et al, 2018]. A recent substructural analysis from the same group showed that a longer duration of alcohol sobriety predicted larger volumes in the hippocampal CA1 for males, but smaller volumes in this region for females [Sawyer et al, 2019].…”
Section: Substance Use Disordersmentioning
confidence: 98%
“…Functional enrichment analysis of these genes identified several significantly enriched traits in the GWAS catalog: the top two being hippocampal tail volume, and cerebrospinal fluid amyloid beta 1-42 levels (CSF Aβ42). Reduced hippocampal tail volume has been reported in persons with AUD in a recent study (86), as well as in individuals with major depressive disorder (MDD) (87). CSF Aβ42 is one of the biomarkers for mild cognitive impairment and dementia (88), and may also be related to AUD.…”
Section: Roh Segments Associated With Aud Severity In Ai Contain Genes Involved In Lipid Metabolism Oxidative Stress and Inflammatory Resmentioning
confidence: 94%